Nimodipine systemic exposure and outcomes following aneurysmal subarachnoid hemorrhage: a pilot prospective observational study (ASH-1 study) - Mahmoud, Sherif Hanafy; Hefny, Fatma; Isse, Fadumo Ahmed; Farooq, Shahmeer; Ling, Spencer; O'Kelly, Cian; Kutsogiannis, Demetrios James (Frontiers in Neurology, 2024)
Background Nimodipine improves outcomes following aneurysmal subarachnoid hemorrhage (aSAH). Guidelines recommend that all patients should receive a fixed-dose nimodipine for 21 days. However, studies reported variability of nimodipine concentrations in aSAH. It is not clear if reduced systemic exposure contributes to worsening outcomes. The aim of this study was to compare nimodipine systemic exposure in those who experienced poor outcomes to those who experienced favorable outcomes. Methods This was a pilot prospective observational study in 30 adult patients admitted to the University of Alberta Hospital with aSAH. Data were collected from the electronic health records following enrollment. Blood samples were collected around one nimodipine 60 mg dose at a steady state, and nimodipine [total, (+)-R and (−)-S enantiomers] plasma concentrations were determined. The poor outcome was defined as a modified Rankin Scale (mRS) score at 90 days of 3-6, while the favorable outcome was an mRS score of 0-2. The correlation between nimodipine concentrations and percent changes in mean arterial pressure (MAP) before and after nimodipine administration was also determined. Furthermore, covariates potentially associated with nimodipine exposure were explored. Results In total, 20 (69%) participants had favorable outcomes and 9 (31%) had poor outcomes. Following the exclusion of those with delayed presentation (>96 h from aSAH onset), among those presented with the World Federation of Neurological Surgeons (WFNS) grade 3–5, nimodipine median (interquartile range) area under the concentration time curve (AUC0-3h) in those with favorable outcomes were 4-fold higher than in those with poor outcomes [136 (52–192) vs. 33 (23–39) ng.h/mL, respectively, value of p = 0.2]. On the other hand, among those presented with WFNS grade 1–2, nimodipine AUC0-3h in those with favorable outcomes were significantly lower than in those with poor outcomes [30 (28–36) vs. 172 (117–308) ng.h/mL, respectively, value of p = 0.03)]. (+)-R-nimodipine AUC0-3h in those who did not develop vasospasm were 4-fold significantly higher than those who had vasospasm (value of p = 0.047). (−)-S-nimodipine was significantly correlated with percentage MAP reduction. Similar results were obtained when the whole cohort was analyzed. Conclusion The study was the first to investigate the potential association between nimodipine exposure following oral dosing and outcomes. In addition, it suggests differential effects of nimodipine enantiomers, shedding light on the potential utility of nimodipine enantiomers. Larger studies are needed.